2009
DOI: 10.1073/pnas.0908593106
|View full text |Cite
|
Sign up to set email alerts
|

Gasp, a Grb2-associating protein, is critical for positive selection of thymocytes

Abstract: T cells develop in the thymus through positive and negative selection, which are responsible for shaping the T cell receptor (TCR) repertoire. To elucidate the molecular mechanisms involved in selection remains an area of intense interest. Here, we identified and characterized a gene product Gasp (Grb2-associating protein, also called Themis) that is critically required for positive selection. Gasp is a cytosolic protein with no known functional motifs that is expressed only in T cells, especially immature CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
107
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(117 citation statements)
references
References 41 publications
9
107
1
Order By: Relevance
“…Despite the absence of strong biochemical evidence, it was presumed that Themis1 likely functions as a positive regulator of TCR signaling because several defects in Themis1 −/− mice, such as a marked impairment of both positive and negative selection, were consistent with a deficiency in TCR signaling (2)(3)(4)(5)(6). It was subsequently shown that Themis1 interacts with Vav1 and that Vav1 phosphorylation is reduced in Themis1 −/− thymocytes, results that also implied a positive role for Themis1 in TCR signaling (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the absence of strong biochemical evidence, it was presumed that Themis1 likely functions as a positive regulator of TCR signaling because several defects in Themis1 −/− mice, such as a marked impairment of both positive and negative selection, were consistent with a deficiency in TCR signaling (2)(3)(4)(5)(6). It was subsequently shown that Themis1 interacts with Vav1 and that Vav1 phosphorylation is reduced in Themis1 −/− thymocytes, results that also implied a positive role for Themis1 in TCR signaling (9).…”
Section: Discussionmentioning
confidence: 99%
“…We and others identified the previously uncharacterized protein Themis1 as being required for the positive selection and maturation of T cells in the thymus (2)(3)(4)(5)(6). Themis1 lacks any discernable catalytic domain, but it contains two previously uncharacterized cysteine-based globular domains (named "CABIT") of unknown structure and function (3).…”
Section: Introductionmentioning
confidence: 99%
“…THEMIS expression is high in double-positive (DP) thymocytes, with a marked downregulation after positive selection and in peripheral T cells. Whereas knockout mice did not show hallmarks of autoimmunity (3,5), the recently described BN m rat strain has linked a frameshift mutation in the Themis gene to inflammatory bowel disease caused by defective regulatory T cell function (6). THEMIS is a highly conserved, 73-kDa cytoplasmic protein without any obvious catalytic or protein-protein interaction domains.…”
Section: T Hymocyte-expressed Molecule Involved In Selection (Themis)mentioning
confidence: 99%
“…Bioinformatics analysis predicts a tandem repeat of a novel, cysteine-containing globular domain (cysteine-containing all b in THEMIS [CABIT]) found in a number of metazoan proteins (2). A putative bipartite nuclear localization sequence is present within the CABIT-2 domain of THEMIS, but no nuclear translocation was detected upon TCR ligation (3,5). The C-terminal end of THEMIS, predicted to contain little or no secondary structure, harbors two proline-rich regions (PRRs).…”
Section: T Hymocyte-expressed Molecule Involved In Selection (Themis)mentioning
confidence: 99%
“…Alternatively, but not mutually exclusively, the role of Grb2 in T cell selection might be explained by its ability to recruit a THEMISGrb2-SHP1/2 complex to LAT in the immunological synapse, where THEMIS and SHP1/2 set the threshold for positive selection (6,7). In the absence of THEMIS or if the THEMIS binding site for Grb2 is mutated, positive selection is drastically impaired (5,7,33,34). The importance of the C-terminal SH3 domain of Grb2 that recruits THEMIS (6) is also highlighted by studies in which mutated forms of Grb2 were transduced into bone marrow cells from Grb2 fl/fl Lckcre tg mice via retroviral transduction.…”
Section: Discussionmentioning
confidence: 99%